(Re)Creating a World in Seven Days: Place, Disability and Salvation in Extreme Makeover: Home Edition - Emily Askew (Disability Studies Quarterly, 2011)
At its most superficial rhetorical level, ABC’s hit television show, Extreme Makeover: Home Edition, equates the condition of the family home with the condition of the bodies inside the home. If the home is ‘fixed’, then the people who live in that home will be 'fixed', as well. In this essay, I consider the ways that Extreme Makover: Home Edition constructs the human body as disabled through the medium of architecture, helped along by reality television’s version of Christian sacrificial atonement.
Keywords: salvation; creation; God; Jesus; place; extreme makeover; makeover television; sin; agency; essentialism; freaks